Preparation and Evaluation of Blood Compatibility of NovelEpoxy-Modified Polyurethanes: Blood compatible polyurethanes - Atefeh Solouck,; Hamid Yeganeh,; Mohammad Rafienia, (Iranian Journal of Pharmaceutical Sciences, 2008)
In order to prepare polyurethane elastomers with acceptable physical properties and good biocompatibility, novel polyurethane networks were synthesized via curing reaction of epoxy-terminated polyurethane prepolymers (EUPs) with hexamethylene diamine. EUPs were prepared from reaction of glycidol with NCO-terminated polyurethanes (ITPs). ITPs were also synthesized from reaction of one equivalent of either poly(tetramethylene ether)glycol or poly(ethylene glycol) with hexamethylene diisocyanate. Cytotoxcicity and blood compatibility were evaluated.All of the prepared polymers via this novel and simple method showed nontoxic behavior and acceptable blood compatibility.